Evolution of soil organic carbon during a chronosequence of transformation from cacao (Theobroma cacao l.) plantation to grassland - Pedro Salvador Morales; Ruffo Sanchez Hernandez; Delfino Sánchez Gómez; Ulises López Noverola; Gelacio Alejo Santiago; Eduardo Valdés Velarde; Juan Fernando Gallardo Lancho (Acta Agronómica)
The aim of this research was to evaluate the impact of the soil use change of the Cocoa Agroforestry System (CAS) on soil organic carbon (SOC) levels and other indicating soil chemical fertility properties (apparent density ρb, cation exchange capacity CEC, total soil N TSN), when a soil use change occurs from CAS to grassland (GL). For this, in order to be selected was recorded, considering different time intervals (1-5, 6-10 y 11-20 years). However, a CAS of 20-35 years was considered as a reference. In addition, soil samples were taken at -30 cm depth to determine the contents of SOC, TSN, CEC, ρb, soil organic matter (SOM) and the soil C/N relationship. Consequently, an in situ resistance to soil penetration was evaluated. The results indicated the change in soil use from CAS to GL, did not cause a significant decrease in the amount of stored SOC (0-30 cm) during the considered time with respect to CAS. However, if only the first -10 cm of soil is sampled, a significant soil compaction is observed throughout a decrease in the CEC value in the long term (20 years).